2007
DOI: 10.1111/j.1365-2451.2007.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

The Purbeck Limestone Group of Dorset, southern England

Abstract: The late Jurassic to early Cretaceous Purbeck Limestone Group of Dorset has been a focus for media and academic attention for the last 150 years. For example, The Illustrated London News in 1857 carried an article by the Revd Charles Kingsley, (of The Water Babies fame), titled ‘Geological Discoveries at Swanage’. describing fossil‐hunting endeavours of Samuel Husband Beckles (1814–1890; Fig. 1). Beckles had been encouraged by Richard Owen (1804–1892) to go in search of the tiny fossilized mammalian remains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…The bowl-like form of the Brachiosaurus pes ( figure 7) is reminiscent of a number of reported sauropod tracks (e.g. [59,60]). The simulations here indicate that such a bowl-like form is potentially characteristic of undertracks.…”
Section: Discussion Of Individual Track Featuresmentioning
confidence: 94%
“…The bowl-like form of the Brachiosaurus pes ( figure 7) is reminiscent of a number of reported sauropod tracks (e.g. [59,60]). The simulations here indicate that such a bowl-like form is potentially characteristic of undertracks.…”
Section: Discussion Of Individual Track Featuresmentioning
confidence: 94%
“…Although thoroughly studied and reviewed (see Clements, 1993; Westhead & Mather, 1996; Ensom, 2002), many stratigraphical proposals have been adopted for the PLG. Here we follow the functional divisions of Westhead & Mather (1996), because of their basin‐wide mappability, and the bedding divisions of Clements (1993), which provide a comprehensive distribution of sediments in the area of collection (Durlston Bay).…”
Section: Geologymentioning
confidence: 99%
“…Eggshell studied by Ensom (1997Ensom ( , 2002 and identified as of the dinosaur-spherulitic morphotype from different localities of the Purbeck facies (Berriasian) is here assigned to Mycomorphoolithus sp. This oogenus occurs throughout for most of the Early Cretaceous, coexisting with Krokolithidae eggshells, which are more similar to the eggshells of modern crocodiles.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of incipient pore openings and dissolution pits in the eggshell surface suggest that degradation may have an important role in this process. Ensom (1997) in his initial studies in the Berriasian English materials previously reported Type 1 and Type 2 eggshells as a single eggshell type. We think that this interpretation is more plausible, and that Type 2 eggshells represent the final stage of pore development, as in the Iberian eggshells (category d), the eggshells reported as cf.…”
Section: Eggshell Porosity and Extrinsic Degradationmentioning
confidence: 97%